Vegetative development of pitaya genotypes under the effect of different doses of biostimulant - Cardoso, Jackson Felipe (2024)
Pitaya exhibits great rusticity and productive potential, in addition to interesting and appealing physical, nutritional, and sensory attributes for a healthy diet. As the main propagation method in the field, cuttings aim for early and uniform orchard establishment. To enhance seedling quality, the use of biostimulants is an option to assist in rooting. The aim of this study was to evaluate the rooting and the sprouting of pitaya cuttings concerning different concentrations of a seaweed-based biostimulant, SprintAlga TS® (Biolchim), applied at different time intervals. The research was conducted from September 2022 to January 2023, at the Federal University of Santa Catarina (UFSC) in Florianópolis, state of Santa Catarina, Brazil. The evaluated genotypes were Hylocereus polyrhizus, Selenicereus undatus, Golden (Selenicereus undatus), Selenicereus costaricensis and Selenicereus setaceus. The used vegetative material came from the Experimental Station of EPAGRI, in Itajaí, state of Santa Catarina, and the cuttings were standardized in 20 cm length. The cuttings were kept in a shaded environment for 21 days and rooted at a depth of 5 cm, individually in two-liter plastic bags filled with substrate. The experiment consisted of three treatments: the first involving only irrigation with water (control), the second with application of biostimulant at 22 and 52 days after cuttings planting, and the third also with application of biostimulant at 10, 22, 36 and 52 days after planting. The use of the seaweed extract-based biostimulant proved effective for the propagation of the genotypes S. undatus and Golden. However, the four times application negatively affected the root development of the S. setaceus genotype. The genotypes S. costaricensis and S. setaceus exhibited lower vigor in vegetative development compared to the genotypes H. polyrhizus, S. undatus, and Golden. It was concluded that the use of seaweed extract as a biostimulant had varied effects on the different evaluated genotypes.